MENCEGAH RESIKO BENCANA ALAM MERAPI MELALUI KEGIATAN PENYULUHAN DAN PEMASANGAN PETUNJUK ARAH KUMPUL BERSAMA MAHASISWA DAN MASYARAKAT DUSUN GANJURAN WEDOMARTANI, SLEMAN - Judha, Mohamad (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2025)
Mount Merapi as an active volcano in the world, is located in two densely populated provinces, the eruption of Mount Merapi forced people to evacuate, several other consequences caused loss of life and property. One of the areas most severely affected by the 2010 eruption was 32 fatalities in Sleman district, some of which were in Ganjuran hamlet, this was due to the lack of socialization on how to deal with disasters. In this community service activity, it is divided into pre-activities, implementation of community service activities, monitoring and evaluation of activities. Pre-activities begin with a preliminary survey of the community around the disaster about community knowledge about the Mount Merapi disaster, then continued with education. The next activity is mapping the potential dangers if a disaster occurs accompanied by the installation of evacuation directions at six points in Ganjuran hamlet towards a safe area for evacuation and counseling on efforts to reduce victims of volcanic eruptions. After health counseling, the post-test results increased significantly. The evaluation results showed efforts to increase volcanic disaster preparedness 78.26%, disaster evacuation efforts 91.30%, the role of the community in evacuating disaster victims 78.26%. Participants also got an overview of the benefits of installing evacuation routes in Ganjuran hamlet and felt more prepared to face disasters after attending the training. In conclusion, Community service in the context of volcanic disasters in Indonesia shows positive results in improving disaster preparedness and mitigation.